Trigonometry! #31

Geometry Level 4

Find the value of cos ( 2 cos 1 x + sin 1 x ) \cos(2\cos^{-1}x + \sin^{-1}x) at x = 1 5 x=\frac {1}{5} , where 0 cos 1 x π 0≤\cos^{-1}x≤\pi and π 2 sin 1 x π 2 \frac {-\pi}{2} ≤ \sin^{-1}x ≤ \frac {\pi}{2} .

If your answer is in the form of a b c -\frac {a\sqrt{b}}{c} , where b b is a square free integer, enter the value of a + b + c a+b+c .

This problem is part of the set Trigonometry .


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jan 18, 2015

Let α = cos 1 1 5 \space\alpha = \cos ^{-1} {\frac{1}{5}}\space and β = = sin 1 1 5 \space \beta = = \sin ^{-1} {\frac{1}{5}} . Then, we have:

cos ( 2 cos 1 1 5 + sin 1 1 5 ) = cos ( 2 α + β ) \cos {(2\cos ^{-1} {\frac{1}{5}}+ \sin^{-1} {\frac{1}{5}})} = \cos {(2\alpha+\beta)}

= cos 2 α cos β sin 2 α sin β \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad = \cos {2\alpha}\cos{\beta} - \sin {2\alpha}\sin{\beta}

= ( cos 2 α 1 ) cos β 2 sin α cos α sin β \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad = (\cos^2 {\alpha}-1)\cos{\beta} - 2\sin {\alpha}\cos{\alpha}\sin{\beta}

= ( 1 25 1 ) cos β 2 ( 1 25 ) sin α \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad = (\frac{1}{25}-1)\cos{\beta} - 2(\frac{1}{25})\sin {\alpha}

= ( 1 25 1 ) 1 1 25 2 25 1 1 25 \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad = (\frac{1}{25}-1)\sqrt{1-\frac{1}{25}} - \frac{2}{25}\sqrt{1-\frac{1}{25}}

= ( 23 25 2 25 ) 24 25 = 2 6 5 \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad = \left( -\frac{23}{25} - \frac{2}{25} \right) \sqrt{\frac{24}{25}} = - \frac {2\sqrt{6}}{5}

a + b + c = 2 + 6 + 5 = 13 \Rightarrow a + b + c = 2+6+5 = \boxed{13}

c o s ( π 2 + c o s 1 x ) = s i n ( c o s 1 x ) = 1 x 2 cos( \dfrac{\pi}{2} + cos^{-1}x) = -sin(cos^{-1}x) = - \sqrt{1 - x^2}

= 2 6 5 = \dfrac{-2\sqrt{6}}{5}

U Z - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...